The Role of Psychological Safety and Psychological Empowerment on Intrapreneurial Behavior towards Successful Individual Performance: A Conceptual Framework (Sains Humanika, 2018)
Though a substantial number of researches have been documented between psychological safety, psychological empowerment and individual level performance, the manner through which these relationships transpires is scarcely studied, principally as regards to individual performance of middle managers in medium enterprises. To address this shortfall and to expound further on these relationships, several researchers proposed mediating variables to better explain the relationship between these variables. Accordingly, this paper proposes intrapreneurial behavior as a mediating variable on the psychological safety, psychological empowerment and individual level performance relationships of middle managers in Nigerian medium enterprises. Psychological safety, psychological empowerment and intrapreneurial behavior relationships have been deliberated, followed by the intrapreneurial behavior and middle manager successful performance relationship and lastly the proposed mediating role of intrapreneurial behavior on the psychological safety, psychological empowerment and individual level performance relationships.
Keywords: Psychological safety; psychological empowerment; intrapreneurial behavior; individual performance; middle managers; Nigeria.